Trabzon Erzurum İmtidadî buharlı nakliyat anonim şirketi - (:unkn) unknown (My University, 2010)
Bu çalışmada Başbakanlık Osmanlı Arşivi’nde Ticaret ve Nafıa Nezareti evrakı arasında bulunan, Erzurum-Trabzon arasında buharlı arabalarla eşya, yolcu ve posta nakliyatı yapmak için imtiyaz isteyen Fransız Bonşu’nun bölgede yaptığı saha araştırması sonucu kurmak istediği ‘Trabzon Erzurum İmtidadî Buharlı Nakliyat Anonim Şirketi’ne ait proje raporunu incelenmektir. Raporda, bölge yollarının mevcut durumlarına, yolcu ve eşya nakliye kapasitelerine değinilmiştir. Ayrıca imtiyaz isteğini ileten müteşebbisin mevcut yol ve nakliye sorunlarının çözümüne dair önerileri de raporda yer almıştır. Bölgenin Rusya, İran ve Osmanlı Devleti arasındaki ticarette kilit bir rol üstlendiğini hatırlatan müteşebbis, ulaşımın hız kazanmasıyla birlikte Osmanlı Devleti ve tebaasının bundan kazançlı çıkacağını belirtmiştir. İmtiyaz isteği, bölge yetkililerince olumlu karşılanmış ve buharlı araçların sağlayacağı yararlar ayrıntılı olarak valilik layihasında tasvir edilmiştir. Ne var ki proje, çeşitli sebeplerden ötürü hayata geçirilememiştir.

This study aims to clarify on the report the project of ‘Trabzon-Erzurum Permanent Vaporous Transport Co.’ prepared by a French man, Mr. Bonşu, in order to get a concession for transportation of goods, passengers and mail with vaporous (steam) vehicles. The project’s document can be found in folder of Ministry of Trade and Public Works in Prime Ministry Ottoman Archives, Istanbul. In the report, the current status of regional roads and transportation capacity of passengers and goods has been discussed. Moreover, recommendations for the solution of problems concerning to the existing road and transportation took place in the report of the entrepreneur who submits requests to the privileges. The French entrepreneur, reminding the region’s key role for trade conducted between the Ottoman State, Russia and Iran, has indicated that both the Ottoman State and its subjects will be benefited from the high-speed trade performed through vaporous (steam) vehicles. Concession request has been welcomed by the regional authorities and the benefits of vaporous (steam) vehicles have been described in detail by Governor Pleading. On the other hand, due to some reasons the project could not be executed.
Trabzon-Erzurum permanent vaporous transport Co.
Keywords: Tarih